Kant's Pre-Critical Period Concept of Time - Küçükparmak, Aykut (MUSTAFA CEVIK, 2017)
His views of the nature of the time play an important role in the understanding of Kant's philosophy. Whereas Kant's views on the nature of time are relatively neglected. In this framework, an examination on his theory of time seems necessary. Kant has adopted different opinions on the nature of time during the his life of thought. These differences most manifest themselves in pre and post-critical period thoughts. The main purpose of this work is to prepare the ground for understanding the Kant's critical period thoughts by revealing the his pre-critical period time theory.
Keywords: Kant; pre-critical period; time; the nature of time; time and space